A linkage map for the B-genome of Arachis (Fabaceae) and its synteny to the A-genome - Moretzsohn, Marcio C.; Barbosa, Andrea V. G. [UNESP]; Alves-Freitas, Dione M. T.; Teixeira, Cristiane; Leal-Bertioli, Soraya C. M.; Guimaraes, Patricia M.; Pereira, Rinaldo W.; Lopes, Catalina R. [UNESP]; Cavallari, Marcelo M. [UNESP]; Valls, Jose F. M.; Bertioli, David J.; Gimenes, Marcos A. (Biomed Central Ltd., 2009)
Background: Arachis hypogaea (peanut) is an important crop worldwide, being mostly used for edible oil production, direct consumption and animal feed. Cultivated peanut is an allotetraploid species with two different genome components, A and B. Genetic linkage maps can greatly assist molecular breeding and genomic studies. However, the development of linkage maps for A. hypogaea is difficult because it has very low levels of polymorphism. This can be overcome by the utilization of wild species of Arachis, which present the A- and B-genomes in the diploid state, and show high levels of genetic variability.Results: In this work, we constructed a B-genome linkage map, which will complement the previously published map for the A-genome of Arachis, and produced an entire framework for the tetraploid genome. This map is based on an F2 population of 93 individuals obtained from the cross between the diploid A. ipaensis (K30076) and the closely related A. magna (K30097), the former species being the most probable B genome donor to cultivated peanut. In spite of being classified as different species, the parents showed high crossability and relatively low polymorphism (22.3%), compared to other interspecific crosses. The map has 10 linkage groups, with 149 loci spanning a total map distance of 1,294 cM. The microsatellite markers utilized, developed for other Arachis species, showed high transferability (81.7%). Segregation distortion was 21.5%. This B-genome map was compared to the A-genome map using 51 common markers, revealing a high degree of synteny between both genomes.Conclusion: The development of genetic maps for Arachis diploid wild species with A- and B-genomes effectively provides a genetic map for the tetraploid cultivated peanut in two separate diploid components and is a significant advance towards the construction of a transferable reference map for Arachis. Additionally, we were able to identify affinities of some Arachis linkage groups with Medicago truncatula, which will allow the transfer of information from the nearly-complete genome sequences of this model legume to the peanut crop.